1989
DOI: 10.1073/pnas.86.18.7128
|View full text |Cite
|
Sign up to set email alerts
|

Two proteins targeted to the same lytic granule compartment undergo very different posttranslational processing.

Abstract: The granules of natural killer (NK) cells contain cytolysin and serine proteases, proteins that are expressed specifically in cytolytic cells and are released in response to target binding. We have used immunofluorescence and immunoelectron microscopy to localize these proteins with respect to the various morphological compartments of granules in a rat NK cell line. Both cytolysin and the proteases are limited to the core regions of the dense core granules. While these proteins are targeted to the same compart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 34 publications
4
35
0
1
Order By: Relevance
“…In PC12 chromaffin cells, treatment with LatA results in a more rapid expulsion of granule contents, which would be consistent with our observation of shorter persistence of fluorescence post-degranulation (25). Together, these results suggest a requirement for force in fully extracting lytic components from granules, which contain a dense core including extracellular matrix components such as proteoglycans (26, 27). It should also be noted that, while we did not observe a difference in granule velocity or displacement, we did see a significant difference between control and LatA-treated cells in displacement rate, with LatA-treated cells having a significantly lower displacement rate pre-degranulation.…”
Section: Discussionmentioning
confidence: 84%
“…In PC12 chromaffin cells, treatment with LatA results in a more rapid expulsion of granule contents, which would be consistent with our observation of shorter persistence of fluorescence post-degranulation (25). Together, these results suggest a requirement for force in fully extracting lytic components from granules, which contain a dense core including extracellular matrix components such as proteoglycans (26, 27). It should also be noted that, while we did not observe a difference in granule velocity or displacement, we did see a significant difference between control and LatA-treated cells in displacement rate, with LatA-treated cells having a significantly lower displacement rate pre-degranulation.…”
Section: Discussionmentioning
confidence: 84%
“…Granzymes are modified by a mannose-6-phosphate just like lysosomal hydrolases, and their sorting is disrupted when the phosphotransferase that makes this modification is absent in mucolipidosis II (I-cell disease) (Griffiths and Isaaz 1993). However, perforin is not modified with a mannose-6-phosphate, receiving only complex glycans, and cannot use the MPR pathway (Burkhardt et al 1989;Uellner et al 1997). Precisely how perforin is trafficked to the secretory lysosome remains something of a mystery, because disruption of the protein either by truncation or removal of the glycans results in misfolding and degradation when expressed in cells (Uellner et al 1997;Brennan et al 2011).…”
Section: Lysosome Biogenesismentioning
confidence: 99%
“…Some of the early research on the targeting of these proteins revealed that perforin and granzymes followed very different trafficking pathways (Burkhardt et al 1989). Granzymes are modified by a mannose-6-phosphate just like lysosomal hydrolases, and their sorting is disrupted when the phosphotransferase that makes this modification is absent in mucolipidosis II (I-cell disease) (Griffiths and Isaaz 1993).…”
Section: Lysosome Biogenesismentioning
confidence: 99%
“…The presence of perforin in MPRpositive vesicles is somewhat surprising, as perforin has been reported to lack mannose-6-phosphate modification. 37 On the other hand, lysosomal proteins are able to use MPR-positive carrier vesicles even though they do not have the modification; for example, neuraminidase uses the interaction with mannose-6-phosphatemodified cathepsin A to reach lysosomes. 38 Concurring with our findings, a recent report demonstrating the importance of perforin glycosylation in its traffic to lytic granules postulates that perforin primarily uses the MPR-dependent pathway to reach lytic granules.…”
Section: Is Required For Nk-cell Cytotoxicity 4679mentioning
confidence: 99%